Determining factors of FDI flows to selected Caribbean countries - Sandra Sookram; Roger Hosein; Leera Boodram; George Saridakis (Journal of Risk and Financial Management, 2022)
Foreign direct investment (FDI) is a vital ingredient in achieving sustained growth in the Caribbean region. However, FDI inflows have been affected by issues such as market factors, trade barriers, costs factors, investment climate, political and foreign exchange stability. To this end, this paper examines the factors affecting FDI flows into Caribbean countries. We argue that Small Island Developing States in the Caribbean (SIDSC) can be affected by issues such as their small market size, high cost of energy, proneness to exogenous shocks from commodity prices, natural disasters and climate change. A point to note is that countries in the Caribbean with natural resources are expected to have biased FDI inflows. Additionally, countries throughout the Caribbean have different economic and productive structures and unique issues that can affect them based on their individual characteristics. To this end, a panel Autoregressive Distributed Lagged (ARDL) model is used to determine the factors affecting FDI inflows in the Caribbean over the period 2000 to 2019. The findings reveal that GDP growth, natural resource rents, gross capital formation and population growth are significant factors influencing growth in the Caribbean region.
Keywords: 330; foreign direct investment; Small Island Developing States; Caribbean